Kajian Pengembangan Kawasan Sentra Sepatu Cibaduyut yang Berorientasi pada Daya Tarik Wisata Belanja - Theodorus, Arvin; Mawarni, Ida Ayu Sawitri Dian; Mukhlis, Andi M. Ahsan (ATRIUM: Jurnal Arsitektur, 2024)
Title: Study of The Development of Kawasan Sentra Sepatu Cibaduyut Oriented to Shopping Tourism Attraction Kawasan Sentra Sepatu Cibaduyut has a history as a shoe hub Kecamatan Bojongloa Kidul of Bandung City. In 1989, the Government of the Republic of Indonesia officially designated the Kawasan Sentra Sepatu Cibaduyut as a tourist attraction. As a tourist destination, this must consider crucial aspects that influence shopping tourism activities, such as tourism concepts and elements affecting shopping tourism activities. This research focuses on shopping tourism activities in Kawasan Sentra Sepatu Cibaduyut, conducting in-depth interviews with key subjects involved in tourism activities, including shoe manufacturers, shoe material vendors, shoe retailers, and local visitors as research subjects in shopping tourism activities. The interview results are then used to assess the elements of shopping tourism activities within the framework of the fundamental 3A tourism component, which includes attractions, amenities, and accessibility. The synthesis of 3A tourism components with respondent preferences as a result of interviews became the alternative design for developing shopping tourism attractions in Kawasan Sentra Sepatu Cibaduyut. This research has resulted in proposed planning points and the design of new tourist points and activities in Kawasan Sentra Sepatu Cibaduyut, which are oriented toward shopping tourism attractions.